Growth Law For Peritectic Phases Formation In The Zinc Coating - Guzik E.; Kopyciński D.; Wołczyński W. (Archives of Metallurgy and Materials, 2015)
Some experiments dealing with the isothermal hot dip galvanizing were carried out. The (Zn) – coating settled on the Armco-iron substrate were examined after arresting the solidification for different periods of time. The measurement of the thickness of each sub-layer in the coating were performed due to the SEM – analysis. The zinc segregation on the cross-section of the studied sub-layers were also determined by the EDS technique. The growth laws are formulated mathematically for each of the observed sub-layer. The mechanism of the sub-layer formation is also analysed due to the observation of the birth/nucleation of the phases in the sub-layers and the effect of flux onto the sub-layers morphology formation. The appearance of each phase is referred to the Fe-Zn diagram for stable equilibrium according to which these phases are the products of the adequate peritectic transformation.